Effect of different fertilizer treatments on the chemical content of tubers of three spring potato cultivars - Mahmood, Ola Hamzah; Alnuaimi , Jassim Jawad Jader; Al-Zubaidi, Ali Hassan (Journal of Kerbala for Agricultural Sciences, 2024)
The field experiment was carried out in the Musayyib project area, which is located 35 km north of Babylon Governorate, during the fall growing season of 2023 according to a randomized complete block design (RCBD), to determine the effect of biofertilization four levels (0 without adding + full fertilizer recommendation, addition 10g of a mixture of four types of bacterial fertilizer + half the fertilizer recommendation, addition 10g of fungal biofertilizer (mycorrhizal) + half the fertilizer recommendation and addition 10g of a mixture of bacterial and fungal biofertilizers + half the fertilizer recommendation) which is symbolized by (B0, B1, B2 and B3 respectively) and nanofertilizer at two levels (0 + full fertilizer recommendation and 2g L-1+ half the fertilizer recommendation) and denoted by the symbol (N0 and N1, respectively) in the growth and yield of three potato varieties (Rashida, Sifra and Arizona), denoted by the symbol (V1, V2 and V3 respectively). The results showed Arizona variety excellence the rest of the other varieties in the tubers’ content of nitrogen, phosphorus, potassium, protein, and starch. The biofertilization treatment (adding 10g of a mixture of bacterial and fungal biofertilizers) also had a positive effect on the tubers’ content of nitrogen, phosphorus, potassium, protein, and starch compared to the control treatment. The nano-fertilizer addition treatments also had a clear effect on the tubers’ content of nitrogen, phosphorus, potassium, protein, and starch compared to the control treatment. As for the interaction between the study factors, there were significant differences in most of the study traits.